Insight into the gastro-duodenal digestion resistance of soybean proteins and potential implications for residual immunogenicity. Issue 4 (15th March 2017) - De Angelis, Elisabetta; Pilolli, Rosa; Bavaro, Simona L.; Monaci, Linda
Abstract : Soy is an important component of the human diet thanks to its nutritional value and high protein content; however, it also represents a risk for allergenic consumers due to its potential to trigger adverse reactions in sensitized individuals. Abstract : Soy is an important component of the human diet thanks to its nutritional value and high protein content; however, it also represents a risk for allergenic consumers due to its potential to trigger adverse reactions in sensitized individuals. The putative correlation between immunoreactivity and resistance to the human gastrointestinal (GI) digestion has drawn attention to investigating soybean proteins digestibility. In this work, we provided further insights into this field by performing in vitro simulated GI digestion experiments directly on ground soybean seeds, to provide more realistic results obtained from the digestion of the whole food matrix. Soybean digestion products were analyzed by SDS-PAGE followed by untargeted HPLC-MS/MS analysis and the final data were software treated to enable protein/peptide identification. The latter allowed monitoring the proteolytic degradation of the main soybean proteins during the gastric and duodenal phases. In particular, β-conglycinin and trypsin inhibitors showed the highest resistance to the combined activity of GI enzymes, showing a partial degradation at the end of the duodenal phase as ascertained by the strong electrophoretic bands displayed at 50 kDa and 20 kDa, respectively. Glycinin subunits also presented, even if to a lower extent, resistance to the complete proteolytic degradation, as demonstrated by polypeptide fragments with molecular weight lower than 20 kDa displayed in the gel at the end of duodenal digestion. In addition, by bioinformatics analysis it was demonstrated that the GI resistant fragments of the allergenic proteins, β-conglycinin and glycinin, retained in their primary structure linear epitopes potentially able to trigger an immunoreaction when exposed to the intestinal mucosa. Moreover, such resistant peptides also presented a structural homology with epitope sequences recognized in other legume species, presenting a potential risk of adverse cross-reaction for a larger category of allergic consumers.